1996
DOI: 10.1093/rheumatology/35.2.178
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Controlled Study of Low Back School in the General Population

Abstract: SUMMARYThere are no data on the efficacy of a back school in primary prevention of back pain in the general population or on the characteristics of the population who volunteers. After announcement in the local press, 494 healthy adults volunteered and paid for a back school course in Switzerland. A total of 371 controls were matched for sex, age, profession, nationality and back pain. A statistically significant decrease in numbers of doctor's visits was found by the participants during the following 6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 42 publications
0
24
0
1
Order By: Relevance
“…Several recent studies of back schools have found improved intermediate outcomes associated with training, such as increased knowledge, safer behavior, and fewer visits to a doctor, but no reductions in injury rates or sick leave. [22][23][24][25] We developed a back school for the primary prevention of low back injury and evaluated it in a large, randomized, controlled trial in an industrial setting, which included all employees of the two facilities involved. The program's design and its effect on workers' knowledge and behavior have been described elsewhere 26 ; the effect on rates of low back injury is described here.…”
Section: Methodsmentioning
confidence: 99%
“…Several recent studies of back schools have found improved intermediate outcomes associated with training, such as increased knowledge, safer behavior, and fewer visits to a doctor, but no reductions in injury rates or sick leave. [22][23][24][25] We developed a back school for the primary prevention of low back injury and evaluated it in a large, randomized, controlled trial in an industrial setting, which included all employees of the two facilities involved. The program's design and its effect on workers' knowledge and behavior have been described elsewhere 26 ; the effect on rates of low back injury is described here.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Many treatment methods have been developed and utilized to solve this problem. Conservative treatment is the gold standard for treating patients with low back pain (LBP).…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] It is mainly a "therapist-driven" program and is applied to patients who are involved in any of the three phases: primary, secondary, and tertiary rehabilitation. 9 Its purposes lie in educating patients on the nature of their low back disorders, and helping them to form an active and positive attitude.…”
mentioning
confidence: 99%
See 2 more Smart Citations